FACTORS TO CONSIDER WHEN USING QUALITATIVE INTERVIEWS IN DATA COLLECTION - Kelvin M. Mwita (Social Sciences, Humanities and Education Journal (SHE Journal), 2022)
Qualitative interview is the most commonly used data collection method used in qualitative research. Its ability to collect detailed information and offer insights from participants’ feelings and opinions, among other things, have made it a most preferred data collection method for many qualitative researchers. Like any other qualitative data collection methods, it is not immune to criticisms from various scholars, especially those with positivist orientation. This has been motivating various researchers to find different and better ways of conducting qualitative interviews to achieve research goals. This also motivated conducting this study to discuss factors that researchers have to consider when conducting qualitative interviews. The use of secondary data obtained from a systematic literature review of 31 journal articles published by four journals (indexed in Scopus database dedicated to publishing qualitative studies) was done.  Thematic coding was done which led to the identification of seven factors that have to be considered in qualitative interviews. These factors are pilot tests, selection of the right participants, participants’ convenience, sample size, selection of interview questions, cultural dimensions and length of interview sessions. Qualitative researchers are therefore recommended to consider these factors when conducting qualitative interviews. Due to the flexibility expected in qualitative studies, researchers are also reminded to consider the purpose and nature of their studies in the process